Comparative clinical study of preterm and full-term newborn neonatal seizures - Manoel R.R. Holanda; Áurea N. de Melo (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To compare the characteristics of neonatal seizures between preterm and full-term infants in intensive care unit. METHOD: A prospective study was developed with 104 high-risk newborn, 30 preterm and 74 full-term infants, with clinical seizures. The dependent variable was gestational age. Statistical analyses: Fisher's exact test, odds-ratio and Mann Witney U test. RESULTS: There were significant differences (p<0.05): i) premature neonates develop neonatal seizures later, probably related to the etiologies of the seizures; ii) etiologically, there is a predominance of peri-intraventricular hemorrhage in preterm and of asphyxia in full term neonates; iii) clonic seizures are most frequent in preterm and subtle seizures in full term neonates. CONCLUSION: Although the study had a clinical basis, it was possible to identify differences when the dependent variable was gestational age.